Formation feathers - Zamzuri, Azmir (Universiti Putra Malaysia Press, 2015)
Artificial baits are widely used among anglers in Malaysia. It consists in various forms and shapes and the raw materials of the baits could be found from many sources. Nowadays, we can see various forms and shapes of baits available in the market. Basically, the forms and shapes of the baits depend on the fishing methods that been practised such as trawlers, immersion technique and many others. The bait used is also depending on the fishing areas such as the swamps, ponds, and sea.